2019
DOI: 10.1039/c9dt03181b
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Cu(ii) and Cu(i) in Cu ion-doped zeolitic imidazolate frameworks (ZIF-8) for the dehydrogenative coupling of silanes with alcohols

Abstract: Coexistence of Cu(ii) and Cu(i) in Cu ion doped ZIF-8 nanocrystals for dehydrogenative coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Given the formation of polyselenides during charging/ discharging process, the Se 3d spectra shifts back to higher binding energy at the fully sodiation state in Fig. 5e, suggesting the final conversion of polyselenides, presumedly Na 2 Se [14,30]. Dynamic electrochemical responses of the heterostructured electrode can be examined by CV scanning at different scan rates.…”
Section: Ultrafast Ions Transportation Kinetic Analysis Of Mse-mxene Cnrib In Sibsmentioning
confidence: 99%
“…Given the formation of polyselenides during charging/ discharging process, the Se 3d spectra shifts back to higher binding energy at the fully sodiation state in Fig. 5e, suggesting the final conversion of polyselenides, presumedly Na 2 Se [14,30]. Dynamic electrochemical responses of the heterostructured electrode can be examined by CV scanning at different scan rates.…”
Section: Ultrafast Ions Transportation Kinetic Analysis Of Mse-mxene Cnrib In Sibsmentioning
confidence: 99%
“…WP6-MB host-guest complexation was synthesized according to the published procedure [22,24,25], which was fully characterized by 1 H NMR (Figures S1 and S2 in the Supporting Information). Cu/ZIF-8@ZIF-8 was first synthesized according to the published procedure [23,26]. The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed that Cu/ZIF-8@ZIF-8 had typical hexagon morphology, with a diameter of approximately 190-290 nm (Figure 1a,b and Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Cu 2 O/Cu species uniformly dispersed in the carbon skeleton due to the coordination between copper ions and nitrogen sites in PB skeleton. [17] After removal of SiO 2 templates, the HCS/Cu-x was obtained. The coordination between copper ions and nitrogen sites was confirmed by X-ray photoelectron spectroscopy (XPS) characterization of SiO 2 @ PB and SiO 2 @PB/Cu-0.12 (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%